DAMPAK KRISIS GLOBAL TERHADAP LIKUIDITAS BANK DEVISA NASIONAL - Suharyono Suharyono (Politeknik Negeri Bengkalis, 2015)
Abstract: The global crisis has led banks experienced liquidity problems. The measurement of banks' liquidity ratios is useful to assess the composite rating of a bank, as the impact of the global crisis toward the liquidity of foreign exchange banks. This study aimed to determine whether there was significant difference between the liquidity of foreign exchange banks before and after the global crisis. The Bank’s liquidity was measured using liquidity ratios by comparing current assets to current liabilities. The population of this study was 35 foreign exchange banks. The hypothesis was tested by using Mann Whitney non-parametric different-test. The research of this study showed that the liquidity of foreign exchange banks before and during global crisis had a significant difference. While, the foreign exchange banks liquidity during and after the global crisis, and its liquidity before and after the global crisis did not have significant difference. Key words: Liquidity, bank, foreign exchange, crisis, global.